CONTENT MARKETING EFFECTIVENESS TOWARDS CONSUMER’S PERSPECTIVE ON THE NEW PRODUCT LAUNCH. INVESTIGATION STUDY AMONG YOUNG ADULTS IN INDONESIA - Winata J.; Hussain , Ibiwani Alisa; Ahmad , Noraini; R.N. , Abdullah; Majid M. (Electronic Journal of Business and Management, 2021)
Marketing techniques have shifted significantly from physical to digital, with content marketing emerging as a vital subtype. In Indonesia, the ease of internet access and platform variety has made content marketing highly effective, especially for online marketplaces looking to bridge the gap between buyers and sellers cost-effectively. Young adults, who form the majority of social media and e-commerce users, are particularly susceptible to digital marketing influence. This study explores how content marketing impacts consumer perspectives during new product launches. Findings reveal that content marketing is crucial for early product introduction, providing brands with essential access and multiple channels to reach their target audience effectively.